Change in Colorectal Cancer Tests Submitted for Reimbursement in Switzerland 2012-2018: Evidence from Claims Data of a Large Insurance - Rémi Schneider; Markus Näpflin; Lamprini Syrogiannouli; Sarah Bissig; Kali Tal; Jean-Luc Bulliard; Cyril Ducros; Oliver Senn; Kevin Selby; Caroline Bähler; Eva Blozik; Reto Auer (Frontiers Media S.A., 2021)
Objectives: Guidelines recommend colorectal cancer (CRC) screening by fecal occult blood test (FOBT) or colonoscopy. In 2013, Switzerland introduced reimbursement of CRC screening by mandatory health insurance for 50-69-years-olds, after they met their deductible. We hypothesized that the 2013 reimbursement policy increased testing rate.Methods: In claims data from a Swiss insurance, we determined yearly CRC testing rate among 50-75-year-olds (2012-2018) and the association with socio-demographic, insurance-, and health-related covariates with multivariate-adjusted logistic regression models. We tested for interaction of age (50-69/70-75) on testing rate over time.Results: Among insurees (2012:355'683; 2018:348'526), yearly CRC testing rate increased from 2012 to 2018 (overall: 8.1-9.9%; colonoscopy: 5.0-7.6%; FOBT: 3.1-2.3%). Odds ratio (OR) were higher for 70-75-year-olds (2012: 1.16, 95%CI 1.13-1.20; 2018: 1.05, 95%CI 1.02-1.08). Deductible interacted with changes in testing rate over time (p < 0.001). The increase in testing rate was proportionally higher among 50-69-years-olds than 70-75-year-olds over the years.Conclusions: CRC testing rate in Switzerland increased from 2012 to 2018, particularly among 50-69-years-olds, the target population of the 2013 law. Future studies should explore the effect of encouraging FOBT or waiving deductible.